Dinamika Fisika Kimia Air Tambak Udang Vaname (Litopenaeus vannamei) Yang Dipelihara Dengan Sistem Semi Bioflok - Irsyah Rahmi; Diana Arfiati; Muhammad Musa; Karimah Karimah (Postgraduate, University of Mataram, 2023)
Vannamei shrimp (Litopenaeus vannamei) is one of the leading commodities in Indonesian aquaculture. The cultivation potential that is developing at this time is with intensive technology. However, along with the development of intensive technology, it experienced problems, namely crop failure caused by a decrease in water quality. This study aims to examine the physical and chemical dynamics of vannamei shrimp pond water cultivated with a semi-biofloc system. This study used a survey method and was statistically analyzed using Ms. Excel and Principal component analysis (PCA). Physical and chemical parameters of water that are measured and observed include Temperature, Brightness, pH, Dissolved Oxygen, Salinity, Carbon Dioxide (CO2), Total Organic Matter, Nitrate (NO3), Phosphate (PO4-) and Ammonia (NH3). The results showed that all the physical and chemical parameters of pond water experienced daily and weekly fluctuations during shrimp rearing. Average temperature fluctuations during the study ranged from 26.7 – 32.5 oC, brightness ranged from 26.5 – 85.0 cm, pH ranged from 7 – 8 tended to be normal, dissolved oxygen ranged from 5.8 – 8.8 mg/L, salinity ranged from 18.3 – 22.8, carbon dioxide (CO2) average values during rearing were 0 mg/L, TOM ranged from 18.42 – 71.80 mg/l, nitrate 0.022 – 0.136 mg/l, phosphate 0.017 – 0.136 mg/L and ammonia ranging from 0.008 – 0.088 mg/l. While, the results of the PCA analysis show that dissolved oxygen and brightness significantly affect the life of the shrimp that are cultivated. So it can be concluded that the dynamics of the physics-chemistry of water measured during the study showed that dissolved oxygen and brightness fluctuated and affected aquaculture activities.